Prevalence of musculoskeletal disorders among perioperative nurses: a systematic review and META-analysis - Clari, Marco (BMC Musculoskelet Disord, 2021)
BACKGROUND: To evaluate the prevalence of work-related musculoskeletal disorders (WRMSDs) in perioperative nurses and to explore their association with personal characteristics. METHODS: Medline, Cumulative Index to Nursing and Allied Health Literature, Scopus, Web of Science, Cochrane Library and Joanna Briggs Institute Database were systematically searched. A meta-analysis calculating event rates, and relative 95% Confidence Intervals (CI) was performed for each musculoskeletal body region. The contribution of perioperative nurses’ sex, age, and BMI was assessed through a meta-regression. RESULTS: Twenty-two studies, considering 3590 perioperative nurses, were included in the systematic review. The highest prevalence of WRMSDs was found for the lower-back (62%; 95% CI 0.54–0.70), followed by knee (47%; 95% CI 0.36–0.59), shoulder (44%; 95% CI 0.37–0.51), waist (42%; 95% CI 0.31–0.53), neck (39%; 95% CI 0.29–0.51), ankle-feet (35%; 95% CI 0.22–0.51), upper-back (34%; 95% CI 0.25–0.44), hand-wrist (29%; 95% CI 0.20–0.40), and elbow (18%; 95% CI 0.12–0.26). Meta-regression showed that sex, age, and BMI were not significant predictors of low-back disorders (p = 0.69; R(2) = 0). CONCLUSIONS: WRMSDs represent a high prevalence issue among perioperative nurses. Perioperative nurses, in general, are steadily exposed to both physical and temporal risk factors. Further studies should be addressed to identify specific interventions aimed at reducing the burden of WRMSDs including ergonomic education and physical rehabilitation. Our data could be used in future studies as a reference to assess the risk of WRMSDs in other health-care professionals’ population. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12891-021-04057-3.